Resonance suppression and quality improvement control strategy for a three-phase grid-connected voltage-source inverter under weak grid conditions - Zhang, Zhi; Li, Yiyun; Zhong, Caomao; Zhang, Zhaoyun (Frontiers in Energy Research, 2023)
The three-phase voltage-source grid-connected inverters suffers from grid-connected current quality problem due to system resonance caused by the under-damping characteristics of the filter and grid impedance on the one hand, and the grid-connected current distortion caused by the high content of low harmonics in the grid voltage on the other hand. To resolve this problem, a current quality improvement control strategy combining capacitor-current feedforward active damping and harmonic virtual impedance reshaping is proposed in this paper by analyzing the mechanism of system resonance and grid-connected current distortion. It is also proposed to determine the virtual impedance parameters by using the root locus method, so as to achieve the purpose of improving the output grid-connected current quality of the three-phase voltage source grid-connected inverter under weak grid conditions. Finally, the correctness and effectiveness of the proposed control strategy are verified by simulation and experiment.